Using Literary Texts in The EFL Classroom: A Pilot Study on First-Year English Majors’ Reading Preferences and Perceptions - Pereszlényi, Anna (Working Papers in Language Pedagogy, 2020)
First-year English majors have to meet new expectations and face new challenges when they enter tertiary education, such as reading English literature and participating in literature classes. Despite the rediscovery of literature in EFL education (Bloemert et al., 2017), secondary schools in Hungary primarily focus on preparing their students for final exams and language exams, thus first-year English majors tend to experience difficulties related to reading in the target language. One possible solution to their difficulties might be the inclusion of literary texts in EFL university courses. The purpose of the present article is to introduce the issue from the students' perspective: it reports on a pilot study whose primary aim is to explore first-year English majors’ reading preferences and their perceptions of using literature in the EFL classroom. The instrument is an online questionnaire and the sample includes 39 first-year university students majoring in English. Based on the results, it may be claimed that students are in favour of using literary texts in the EFL classroom. It is hoped that the findings on students’ reading habits will be beneficial for EFL teachers who plan to incorporate literature into their university courses.